PERBEDAAN MORDANTING TERHADAP HASIL PENCELUPAN ZAT WARNA ALAM AIR LIMBAH PENIRISAN GETAH GAMBIR PADA SUTERA MENGGUNAKAN MORDAN TUNJUNG (FESO4) - Putri, Lolita Aida; Adriani, Adriani; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
This study aims to reveal the color (hue), dark light color (value) and flatness of color on silk dyeing results using waste water draining lymph gambier with mordant lotus (FeSO4). This type of research is the study eksperiment.Variabel this study is variable in pre-mordanting X1, X2 simultaneous-mordanting and post-mordanting X3 and Y differences dyeing results. The type of data is primary data sourced from the 15 panelists were analyzed using one-way ANOVA by SPSS (Statistical Product and Service Solution) version 21.0. Based on research results without mordant color is yellow naples, pre-mordanting dark olive green, simultaneous-mordanting ie olive Darb and post-mordanting is dark olive green. Value is a pre-mordanting is dark, meta-mordanting quite bright, post mordanting very dark while the flatness of color in pre-mordanting and meta-mordanting is average while the average post-mordanting less. Hypothesis test for color light dark obtained F count = 42, 467 and F count flatness color = 17.899 while the value Ftabel = 0.514, if F count> F table = then Ho is rejected, so there is a significant difference to the light and the dark color pre flatness-mordanting, simultaneous-mordanting and post mordanting.Keywords: Mordanting, results of Immersion, Wastewater draining sap Gambir